1991
DOI: 10.2166/wst.1991.0621
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Direct Dye and Acid Dye by Adsorption on Chitosan Fiber – Equilibria

Abstract: The recovery of direct dye and acid dye from dilute aqueous solution by adsorption on chitosan fiber, which is cheaper than an activated carbon fiber, appeared technically and economically feasible. The amounts of adsorption of Brilliant Yellow (direct dye) and Acid Orange II (acid dye) on the chitosan fiber were much larger than that for the activated carbon fiber, though these dyes were adsorbed well on the activated carbon fiber too. The experimental equilibrium isotherms were correlated by B.E.T. equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
1
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 0 publications
8
41
1
1
Order By: Relevance
“…The great dependence of the amount of the bound dye on the pH value of the adsorption bath can be seen, because an acid dye binds to the protonated amino groups 4 in the substrate, and the amounts of the protonated amino group can increase with the drop in the pH of the bath. Therefore, Red 1 was almost adsorbed on the substrate in the buffer solution of pH 7.0, in which the protonated amino groups are only slightly present in the substrate as shown in Figure 4.…”
Section: Effect Of Ph On the Adsorption Of Acid Dyementioning
confidence: 99%
“…The great dependence of the amount of the bound dye on the pH value of the adsorption bath can be seen, because an acid dye binds to the protonated amino groups 4 in the substrate, and the amounts of the protonated amino group can increase with the drop in the pH of the bath. Therefore, Red 1 was almost adsorbed on the substrate in the buffer solution of pH 7.0, in which the protonated amino groups are only slightly present in the substrate as shown in Figure 4.…”
Section: Effect Of Ph On the Adsorption Of Acid Dyementioning
confidence: 99%
“…However, there are many functional groups on its surface, such as =C=O. This material can greatly adsorb significant amounts of pollutants, such as trihalomethanes, bromoform, atrazine, dyes and natural organic matters [11][12][13][14][15] or react with them chemically or physically [16,17]. It is also reported that pH value and temperature has no significant effect on its adsorptive capacity [13].…”
Section: Introductionmentioning
confidence: 99%
“…These results are expected because in the case of chitosan, the pKa value of the amino group (R-NH 2 ) in the structure of chitosan is 6.3 (Uzun 2006), so at lower pH values the deacetylated amino groups in chitosan will be protonated to form -NH 3 + groups and subsequently interact with the sulfonyl groups of acid dye to form the NH 3 + − O 3 SR organic complex. In other words, at acidic pH values protonated amino groups will enhance the electrostatic attractions between dye anions and adsorption sites of chitosan and increase dye adsorption (Guibal 2004;Yoshida et al 1991). The adsorption capacity decreases in alkaline solution because of deprotonating amine groups in chitosan, resulting in poor reaction between adsorbent and dye.…”
Section: Effects Of Dye Concentration Ph and Temperature On Adsorptimentioning
confidence: 99%